RESEARCH EXTRACTED FROM THE DOCTORAL THESIS ON THE PROBLEM OF THE ENFORCEMENT OF CRIMINAL LAWS IN RELATION TO THE PRINCIPLE OF SUPREMACY OF CONSTITUTIONAL RULES AND INTERNATIONAL TREATIES. SUBMITTED TO THE FACULTY OF LAW - ISLAMIC UNIVERSITY IN LEBANON - Alaa Hassan Awad Al-Zaidi (Scholars Digest Publishing, 2024)
Legislation is one of the sources of law in domestic systems, and international treaties are one of the sources of public international law in international systems. International agreements can also be one of the sources of domestic criminal law that the national judge is bound by in the event that the state is bound by the treaty, after ratifying it and taking appropriate legal measures to put it into effect, and in accordance with the necessary procedures required by the constitution for its implementation. The study aims to show the difficulties that hinder the implementation of criminal laws in domestic laws, in light of the existence of international agreements and the supremacy of national constitutions. It also aims to show the relationship between national criminal laws and international treaties, in addition to showing the relationship between the constitution and national criminal law, and identifying the difficulties that hinder the application of domestic legal rules. The reason for choosing the subject of the present study is the lack of expansion in the axes related to it, despite its great importance, especially with regard to studying the conflict between criminal laws and the supremacy of national constitutions and international treaties, and trying to develop possible solutions to address this conflict. A set of results have been reached, the most important of which is that the process of concluding international treaties must result in a practical outcome that is the true fruit of the reason for concluding international treaties if the stages of their legal formation are completed and the necessary conditions are met to be considered a rule of domestic law. The state must commit to implementing those treaties and states must commit through their national courts to applying those provisions and they also apply to all individuals and all state authorities. When the state voluntarily enters into international treaties, it knows that the issue of breaching this obligation or the process of laxity in adhering to it leads to international responsibility against it.
Keywords: Problem, enforcement of laws, criminal law, principle of supremacy, constitutional rules, international treaties, comparative study.